Case report: 5-Fluorouracil treatment in patient with an important partial DPD deficiency - Schmitt, Antonin; Royer, Bernard; Boidot, Romain; Berthier, Joseph; Ghiringhelli, François (Frontiers in Oncology, 2023)
Esophageal cancer is a cancer with poor prognosis and the standard 1st line treatment for metastatic or recurrent EC is systemic chemotherapy with doublet chemotherapy based on platinum and 5-fluorouracil (5-FU). However, 5-FU could be a source of severe treatment-related toxicities due to deficiency of dihydropyrimidine dehydrogenase (DPD). In this case report, a 74-year-old man with metastatic esophageal cancer was found to have partial DPD deficiency based on uracilemia measurements (about 90 ng/mL). Despite this, 5-FU was safely administered thanks to therapeutic drug monitoring (TDM). The case report highlights the importance of TDM in administering 5-FU to patients with partial DPD deficiency, as it allows individualized dosing and prevents severe toxicity.